Effect of magnesium supplementation on glycemic control in type 2 diabetes mellitus: evidence-based case report - Apriyanti G, Anita Janetthe; Sinaga, Wina (World Nutrition Journal, 2025)
Background: Diabetes mellitus is one of the most serious and common chronic diseases, leading to life-threatening, disabling and costly complications, and reducing life expectancy. Poor intracellular magnesium concentration may contribute to insulin resistance, whereas higher magnesium levels are associated with increased insulin sensitivity. This study aimed to investigate the effect of magnesium supplementation on glycemic control in patients with type 2 diabetes. Objective: This study aimed to investigate the effect of magnesium supplementation on glycemic control in patients with type 2 diabetes. Methods: A literature search was conducted using three major databases: PubMed, Cochrane Library, and EBSCOhost. MeSH terms, advanced search, and eligibility criteria were used for title and abstract screening after removing duplicates. Critical assessment tools and levels of evidence of the final articles are based on the Oxford Center for Evidence-Based Medicine. Results: A meta-analysis and two RCTs met the PICO and eligibility criteria. One meta-analysis found that magnesium supplementation significantly reduced fasting blood glucose and HbA1c. One RCT reported that magnesium supplementation significantly improved HbA1c, insulin levels, and HOMA-IR. Another RCT found that there were no differences in HbA1C and continuous glucose monitoring. Conclusion: Magnesium supplementation may have a beneficial effect on glycemic control in patients with type 2 diabetes. However, further research is needed to establish optimal dosage and the most effective form of magnesium supplementation.